Antioxidant, antibacterial activity, and phytochemical characterization of Melaleuca cajuputi extract. Issue 1 (December 2015) - Al-Abd, Nazeh; Mohamed Nor, Zurainee; Mansor, Marzida; Azhar, Fadzly; Hasan, M.; Kassim, Mustafa
Abstract Background The threat posed by drug-resistant pathogens has resulted in the increasing momentum in research and development for effective alternative medications. The antioxidant and antibacterial properties of phytochemical extracts makes them attractive alternative complementary medicines. Therefore, this study evaluated the phytochemical constituents ofMelaleuca cajuputi flower and leaf (GF and GL, respectively) extracts and their antioxidant and antibacterial activities. Methods Radical scavenging capacity of the extracts was estimated using 2, 2-diphenyl-2-picrylhydrazyl and Fe2+ -chelating activity. Total antioxidant activity was determined using ferric reducing antioxidant power assay. Well diffusion, minimum inhibitory concentration, and minimum bactericidal concentration assays were used to determine antibacterial activity against eight pathogens, namelyStaphylococcus aureus, Escherichia coli, Bacillus cereus, Staphylococcus epidermidis, Salmonella typhimurium, Klebsiella pneumonia, Streptococcus pneumoniae, and Pasteurella multocida. We identified and quantified the phytochemical constituents in methanol extracts using liquid chromatography/mass spectrometry (LC/MS) and gas chromatography (GC)/MS. Results This study reports the antioxidant and radical scavenging activity ofM. cajuputi methanolic extracts. The GF extract showed better efficacy than that of the GL extract. The total phenolic contents were higher in the flower extract than they were in the leaf extract (0.55 ± 0.05 and 0.37 ± 0.05 gallic acid equivalent per mg extract dry weight, respectively). As expected, the percentage radical inhibition by GF was higher than that by the GL extract (81 and 75 %, respectively). A similar trend was observed in Fe2+ -chelating activity and β-carotene bleaching tests. The antibacterial assay of the extracts revealed no inhibition zones with the Gram-negative bacteria tested. However, the extracts demonstrated activity againstB. cereus, S. aureus, andS. epidermidis . Conclusions In this study, we found thatM. cajuputi extracts possess antioxidant and antibacterial activities. The results revealed that both extracts had significant antioxidant and free radical-scavenging activity. Both extracts had antibacterial activity againstS. aureus, S. epidermidis, andB. cereus . The antioxidant and antimicrobial activities could be attributed to high flavonoid and phenolic contents identified using GC/MS and LC/MS. Therefore, M. cajuputi could be an excellent source for natural antioxidant and antibacterial agents for medical and nutraceutical applications.